Entrepreneurial DNA : the breakthrough discovery that aligns your business to your unique strengths - Abraham, Joe. (New York : McGraw-Hill, 2011)
"What's your entrepreneurial style? Bill Gates, Michael Bloomberg, and Donald Trump may all be entrepreneurs, but that's where the similarities end. From business planning to finance to marketing, experts have taught that one entrepreneurial size fits all. But it's just not true. Entrepreneurial DNA proves the simple but critical fact that not all entrepreneurs have the same style -- and that discovering your personal strengths, interests, and goals is the key to success or failure. With this groundbreaking book, you'll learn how to assess your "entrepreneurial DNA" and put it to work for you.Are you a Builder? Opportunist? Specialist? Innovator? Using the "BOSI" process, you'll discover your unique entrepreneurial profile, enabling you to create a solid business plan and develop strategies that can't fail.If you're serious about becoming an entrepreneur, take your first steps with Entrepreneurial DNA"--
Includes index.
Keywords: Success in business -- Psychological aspects; Entrepreneurship; Businesspeople -- Psychology; Business planning; BUSINESS & ECONOMICS / Entrepreneurship